Reviewing opioid use, monitoring, and legislature: Nursing perspectives - Deniece A. Jukiewicz; Aisha Alhofaian; Zenora Thompson; Faye A. Gary (Elsevier, 2017)
The phenomena of prescription opioid misuse and abuse have a complicated history of contributing factors including policies, practices, and prescribing leading to contemporary phenomena. Some factors implicated in the opioid drug abuse problem include inefficient prescribing and improper use, lack of knowledge related to interpretation and assessment of pain levels, and decreased oversight and regulation from government and policy agents. Nurses, often frontline providers, need to be knowledgeable and embrace the guidelines, and necessary implications associated with both prescribing and administration of opioids. Additionally, all providers including physicians, physician assistants, nurse practitioners, and bedside nurses must have a firm understanding of the improper use and abuse of opioids. The examination and review of opioid policies at the state and federal level has revealed inconsistency with regulations, policies, and guidelines that have lead to the current situation. The use of an interdisciplinary team with nurses and various other practitioners is a good strategy to help reduce this problem. Keywords: Abuse, Administration, Legislature, Nursing, Opioid, Overdose, Policy, Prescribing